THE INFLUENCE OF LOCUS OF CONTROL AND EMOTIONAL INTELLIGENCE ON STUDENT ETHICAL BEHAVIOR - Salsabila, Tasya; Wolor, Christian Wiradendi; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This research aims to: 1) To determine the influence of locus of control on ethical behavior of Faculty of Economics student at State University of Jakarta. 2) To determine the influence of emotional intelligence on ethical behavior of Faculty of Economics student at State University of Jakarta. 3) To determine the influence of locus of control and emotional intelligence on ethical behavior of Faculty of Economics student at State University of Jakarta. This study uses quantitative research methods with data analysis techniques in the form of multiple linear regression analysis using SPSS software version 25. The sampling technique used is proportionate stratified random sampling with a total sample of 218 students. This research is a survey-research in the form of a questionnaire to see the effect of locus of control and emotional intelligence on students' ethical behavior. Based on the analysis, it was found that locus of control has a positive and significant effect on ethical behavior, emotional intelligence has a positive and significant effect on ethical behavior, also locus of control and emotional intelligence together have a positive and significant effect on ethical behavior.